Seroprevalence and Risk Factors of the Bluetongue Virus in Cattle in China From 1988 to 2019: A Comprehensive Literature Review and Meta-Analysis - Gong, Qing-Long; Wang, Qi; Yang, Xue-Yao; Li, Dong-Li; Zhao, Bo; Ge, Gui-Yang; Zong, Ying; Li, Jian-Ming; Leng, Xue; Shi, Kun; Liu, Fei; Du, Rui (Frontiers in Veterinary Science, 2021)
Background: Bluetongue caused by the bluetongue virus (BTV) is a non-contagious, and insect-borne disease mainly affecting domestic and wild ruminants. Bluetongue in cattle is associated with vesicular lesions, weight loss, low milk production, and low reproductive capacity. It should not be ignored as it is associated with large economic losses to the livestock breeding industry in China. Although many studies have investigated bluetongue virus infection in cattle, no nationwide study on the prevalence of bluetongue virus infection in cattle from China has yet been conducted. This meta-analysis aimed to evaluate the seroprevalence and risk factors for bluetongue in cattle. Results: We collected 50 publications from 1988 to 2019 through PubMed, ScienceDirect, Chinese Web of knowledge (CNKI), VIP Chinese journal database, and Wanfang database. A total of the pooled bluetongue seroprevalence of 12.2% (5332/87472) in cattle was tested. The point estimate of bluetongue collected from 2001 to 2011 was 22.5% (95% CI: 1.2–58.9), which was higher than after 2012 (9.9%, 95% CI: 3.3–19.4). The analysis of the feeding model subgroup revealed that the seroprevalence of bluetongue was significantly higher (P < 0.05) among free-range cattle (22.5%; 95% CI: 7.7–42.3) than among cattle from intensive farming systems (1.8%; 95% CI: 0.0–6.7). The seroprevalence of bluetongue in different species showed significant variation (P < 0.05), with the highest seroprevalence of 39.8% (95% CI: 18.7–63.0) in buffalo and the lowest seroprevalence of 4.3% (95% CI: 1.2–9.0) in yak. In the zoogeographical division subgroup, the seroprevalence of bluetongue correlated positively within a certain range with the species distribution of Culicoides. Conclusion: Our findings suggested that bluetongue was prevalent in cattle in China. And the contact with sheep, other ruminants or transmission media such as Culicoides may increase the seroprevalence of bluetongue disease in cattle. It is necessary to carry out continuous monitoring of the bluetongue seroprevalence. Moreover, comprehensive and improved strategies, and measures should be implemented to prevent and control the spread of bluetongue.